Contribution of genetic factors to high rates of neonatal hyperbilirubinaemia on the Thailand-Myanmar border. - Germana Bancone; Gornpan Gornsawun; Pimnara Peerawaranun; Penporn Penpitchaporn; Moo Kho Paw; Day Day Poe; December Win; Naw Cicelia; Mavuto Mukaka; Laypaw Archasuksan; Laurence Thielemans; Francois Nosten; et al. (Public Library of Science (PLoS), 2022)
Very high unconjugated bilirubin plasma concentrations in neonates (neonatal hyperbilirubinaemia; NH) may cause neurologic damage (kernicterus). Both increased red blood cell turn-over and immaturity of hepatic glucuronidation contribute to neonatal hyperbilirubinaemia. The incidence of NH requiring phototherapy during the first week of life on the Thailand-Myanmar border is high (approximately 25%). On the Thailand-Myanmar border we investigated the contribution of genetic risk factors to high bilirubin levels in the first month of life in 1596 neonates enrolled in a prospective observational birth cohort study. Lower gestational age (<38 weeks), mutations in the genes encoding glucose-6-phosphate dehydrogenase (G6PD) and uridine 5'-diphospho-glucuronosyltransferase (UGT) 1A1 were identified as the main independent risk factors for NH in the first week, and for prolonged jaundice in the first month of life. Population attributable risks (PAR%) were 61.7% for lower gestational age, 22.9% for hemi or homozygous and 9.9% for heterozygous G6PD deficiency respectively, and 6.3% for UGT1A1*6 homozygosity. In neonates with an estimated gestational age ≥ 38 weeks, G6PD mutations contributed PARs of 38.1% and 23.6% for "early" (≤ 48 hours) and "late" (49-168 hours) NH respectively. For late NH, the PAR for UGT1A1*6 homozygosity was 7.7%. Maternal excess weight was also a significant risk factor for "early" NH while maternal mutations on the beta-globin gene, prolonged rupture of membranes, large haematomas and neonatal sepsis were risk factors for "late" NH. For prolonged jaundice during the first month of life, G6PD mutations and UGT1A1*6 mutation, together with lower gestational age at birth and presence of haematoma were significant risk factors. In this population, genetic factors contribute considerably to the high risk of NH. Diagnostic tools to identify G6PD deficiency at birth would facilitate early recognition of high risk cases.